Identifikasi Gaya Belajar Siswa dan Dampaknya terhadap Hasil Belajar: Analisis pada Tingkat Pendidikan Menengah Atas - Rusli, Rusli; Suwatno, Suwatno; Rasto, Rasto; Muhammad, Ilham (LP. Ma'arif Janggan Magetan, 2023)
This research is based on the learning outcomes in economics subjects which are still low and the desire to identify trends in students' visual, auditory, and kinesthetic learning styles in economics subjects. With this identification, it is hoped that the teacher will find an effective way as a learning strategy in presenting learning and students will find the most suitable learning method for themselves in receiving learning information. This study uses a quantitative descriptive method. Data collection was carried out using a visual, auditory, and kinesthetic learning style questionnaire. Descriptive statistics are used to analyze the data then look for trends in each student's learning style and calculate the percentage of students as a whole. The research results are as follows. First, the tendency for visual student learning styles is 45% at high levels, 40% medium, and 15% low. The tendency of auditory student learning styles is 21% at high levels, 70% moderate, and 9% low. The tendency of kinesthetic student learning styles is 4% at high levels, 66% moderate, and 30% low. Second, social studies class XI students at Rokan Hulu District Public High School have a visual learning style tendency of 33%, 38% auditory, and 29% kinesthetic students. Third, the average score for students with a visual learning style is 72.4 and the average score for students with an auditory learning style is 77.8 and the average score for students with a kinesthetic learning style is 69.5. Students with an auditory learning style have an average learning result that is better than those with visual and kinesthetic learning styles.